Structural Analysis Of Imperative Sentences On The Medicine Brochures - Aqmarina, Anisa; , Dra. M. Laila, M. Hum; , Drs. Sigit Haryanto, M. Hum (2013)
This study aims to identify the types of imperative sentences on the medicine brochure andto describe the syntactic structure of imperative sentences on the medicine brochure. The type of this research is descriptive qualitative. The writer uses medicine brochures as the data source. The method of collecting data is documentation with the techniques of reading, identifying, and classifying the data. In analyzing the data, the writer identifies the types of imperative sentences using theory of grammatical structure from Quirk (1983) and describes the syntactic structure of imperative sentence using Chinese boxes from Francis (1958). The result of this study shows that (1) imperative sentence on the medicine brochure can be divided into two types: imperative sentence without a subject and negative imperative sentence, (2) there are six types of syntactic structure of imperative sentence in the medicine brochure: syntactic structure of modification , syntactic structure of modification + structure of predication, syntactic structure of complementation + structure of modification, syntactic structure of complementation + structure of coordination + structure of modification, syntactic structure of modification + structure of coordination, and syntactic structure of complementation + structure of coordination.